2016
DOI: 10.1016/j.enpol.2016.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Business models and financing options for a rapid scale-up of rooftop solar power systems in Thailand

Abstract: Business models and financing options play a large role in driving the expansion of rooftop solar markets. In Thailand, even though there is currently a pause in feed-in tariff support for rooftop solar systems, the market is moving forward with new business models and financing options for solar roofs. After reviewing United States-based business models and financing options, this study documents and analyses four emerging business models and one emerging financing option for customers to invest in rooftop so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 23 publications
(25 reference statements)
0
26
0
2
Order By: Relevance
“…The conversion from a group to another group is possible. In another publication [31], they found that electricity bill savings are the essential motive to install a PV system in their houses (66.7%). The second most is costs efficient system which is accounted for 50%.…”
Section: Market Segmentations Of Solar Pv Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion from a group to another group is possible. In another publication [31], they found that electricity bill savings are the essential motive to install a PV system in their houses (66.7%). The second most is costs efficient system which is accounted for 50%.…”
Section: Market Segmentations Of Solar Pv Usersmentioning
confidence: 99%
“…Electricity saving is considered as the essential motive in adopting a PV system [31]. The payback period, especially for energy, should always be one of the criteria used for comparing the viability of one renewable technology against another.…”
Section: Payback Periodmentioning
confidence: 99%
“…The community-shared model (also known as shared solar, community solar or community-owned) is a good opportunity for innovation and to increase the competitiveness of RE technologies. Its biggest advantage is the economy of scale to bring down the PV system costs [129,143]. This model helps communities to acquire and manage their rooftop PV systems, sharing capital and O&M costs [143,144].…”
Section: Business Model Proposal For Re Introductionmentioning
confidence: 99%
“…Its biggest advantage is the economy of scale to bring down the PV system costs [129,143]. This model helps communities to acquire and manage their rooftop PV systems, sharing capital and O&M costs [143,144]. Policy-makers favor the establishment of cooperatives to involve a wider population through solar access distribution [143].…”
Section: Business Model Proposal For Re Introductionmentioning
confidence: 99%
“…As both renewable technologies have environmental life-cycle impacts significantly less than conventional energy sources, the analysis provides insights for decision-makers in Thailand and across ASEAN to consider when developing distributed generation (DG) power [13,23]. Thailand faces renewed energy security issues and this analysis can provide some insights on how to use existing energy and resources in an efficient matter to get the most energy output for energy invested in developing mini-hydro or solar PV systems [28,29].…”
Section: Introductionmentioning
confidence: 99%